1999
DOI: 10.1007/s004170050333
|View full text |Cite
|
Sign up to set email alerts
|

Cellular transport of subretinal material into choroidal and scleral blood vessels: an electron microscopic study

Abstract: Subretinal injection was confirmed as a suitable method for placing fluids into the subretinal space without affecting the morphology of the retina. Subretinal injected material was shown to be incorporated into lysosomes and melanosomes of RPE cells. The injected material was subsequently transported through Bruch's membrane to be finally removed from the eye via choroidal and scleral veins, the process involving macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…These macrophages migrated through the Bruch's membrane and took up lipofuscin granules. Moreover, in a previous work from our group, we have shown that a cellular transport of subretinal material into choroidal and scleral blood vessels involving macrophages can take place [39].…”
Section: Discussionmentioning
confidence: 84%
“…These macrophages migrated through the Bruch's membrane and took up lipofuscin granules. Moreover, in a previous work from our group, we have shown that a cellular transport of subretinal material into choroidal and scleral blood vessels involving macrophages can take place [39].…”
Section: Discussionmentioning
confidence: 84%